Sistem Absensi Online Berbasis Website Studi Kasus: Program Studi Ilmu Komputer Universitas Pat Petulai - Karlina K, Yuni; Andayani, Nurfitri; Murlena, Murlena (Arcitech: Journal of Computer Science and Artificial Intelligence, 2023)
The Computer Science Study Program at Pat Petulai University is currently still adopting a conventional or manual attendance system, both in implementing and managing attendance data, so there is a need for a website that can manage attendance data and processes online. Based on these problems, this research aims to build a website-based online attendance system that can manage attendance data and processes online without having to do it manually or conventionally. By using qualitative descriptive research methods in this research, it is hoped that it can explain the results of the research that has been carried out. The use of information technology in this attendance was made with PHP, MySQL as a database and Laravel framework. System design using Unifed Modeling Language (UML) and waterfall tools as software development methods. The results of the software were tested in terms of functionality using black box testing. With the website that has been built, it is hoped that it can support the progress of the Pat Petulai University Computer Science Study Program in terms of managing student attendance data.